Um estudo sobre gestão de documentos arquivísticos digitais na administração pública federal brasileira - Rocco, Brenda Couto de Brito (2013)
To analyze the problem of digital documents to record management in Brazilian Federal Public Administration, taking as its starting point a study on the use of Information Technologies and Communication in the production and dissemination of digital documents in society. This research aims to analyze the development of the digital record management in Brazil and how it has been applied in the digital medium. The increase in the recording of information into digital documents and the right to access information give increasing importance to study on the digital record management in Brazil, especially in the digital environment. The theoretical sought in Archival Science in Information Science and Diplomatic concepts from which the questions of this paper were presented. To conclude, to present the actual scenario about the digital archival documents within the Federal Public Administration and considers the directions that record management of these documents has taken in Brazil